Determinants of CREB degradation and KChIP2 gene transcription in cardiac memory - Özgen, Nazira (2010)
BACKGROUND: Left ventricular pacing (LVP) to induce cardiac memory (CM) in dogs results in a decreased transient outward K current (I(to)) and reduced mRNA and protein of the I(to) channel accessory subunit, KChIP2. The KChIP2 decrease is attributed to a decrease in its transcription factor CREB (cAMP response element binding protein). OBJECTIVE: To determine the mechanisms responsible for the CREB decrease that is initiated by LVP. METHODS: CM was quantified as T wave vector displacement in 18 LVP dogs. In 5 dogs, Ang II receptor blocker, saralasin, was infused before and during pacing. In 3 dogs, proteasomal inhibitor, lactacystin, was injected into the left anterior descending artery before LVP. Epicardial biopsies were taken before and after LVP. Neonatal rat cardiomyocytes (NRCM) were incubated with H(2)O(2) (50 μmol/L) for 1h with or without lactacystin. RESULTS: LVP significantly displaced the T wave vector and was associated with increased lipid peroxidation and increased tissue Ang II levels. Saralasin prevented T vector displacement and lipid peroxidation. CREB was significantly decreased after 2h of LVP and was comparably decreased in H(2)O(2)–treated NRM. Lactacystin inhibited the CREB decrease in LVP dogs and H(2)O(2) -treated NRM. LVP and H(2)O(2) both induced CREB ubiquitination and the H(2)O(2)-induced CREB decrease was prevented by knocking down ubiquitin. CONCLUSION: LVP initiates myocardial Ang II production and ROS synthesis leading to CREB ubiquitination and its proteasomal degradation. This sequence of events would explain the pacing-induced reduction in KChIP2, and contribute to altered repolarization and the T wave changes of cardiac memory.